2013
DOI: 10.1007/s13238-012-2108-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune plexins and semaphorins: old proteins, new immune functions

Abstract: Plexins and semaphorins are a large family of proteins that are involved in cell movement and response. The importance of plexins and semaphorins has been emphasized by their discovery in many organ systems including the nervous (Nkyimbeng-Takwi and Chapoval, 2011; McCormick and Leipzig, 2012; Yaron and Sprinzak, 2012), epithelial (Miao et al., 1999; Fujii et al., 2002), and immune systems (Takamatsu and Kumanogoh, 2012) as well as diverse cell processes including angiogenesis (Serini et al., 2009; Sakurai et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 96 publications
(143 reference statements)
0
55
0
Order By: Relevance
“…Perturbations of Sema signaling lead to abnormal immune cell migration in vitro and Sema knockout mice exhibit defective immune cell migration and function (reviewed in (13,174,175)). Recent studies have begun to uncover how immune cell migration events are mediated by Semas.…”
Section: Physiological Functionsmentioning
confidence: 99%
“…Perturbations of Sema signaling lead to abnormal immune cell migration in vitro and Sema knockout mice exhibit defective immune cell migration and function (reviewed in (13,174,175)). Recent studies have begun to uncover how immune cell migration events are mediated by Semas.…”
Section: Physiological Functionsmentioning
confidence: 99%
“…Semaphorins have been found to function outside the nervous system serving as regulators of cell proliferation and migration and activators of lymphocytes (Kolodkin et al, 1993;Roney et al, 2013). Semaphorins and plexins are expressed in a variety of tissues besides the nervous system.…”
Section: Neoplasia and Angiogenesismentioning
confidence: 99%
“…Finally, in vivo tumorangiogenic assays demonstrated that Sema4D alone can elicit a significant angiogenic response to promote tumor growth independently of VEGF. Semaphorin-plexin interactions have already been implicated in a variety of responses, including epithelial cell contact modification and branching morphogenesis, regulation of pathological angiogenesis, tissue organization during development, and immune responses (Kolodkin et al, 1993;Roney et al, 2013). Over expression of Sema4D may provide tumors with the potential to support much denser cell populations, thus limiting the space for large fluid-filled cysts, and favoring the formation of much smaller fluid-filled cysts.…”
Section: Lentiviral Vector System Of Gene Transfermentioning
confidence: 99%
“…New factor revealed will allow one to examine specifically its role in the NK-DC crosstalk in tumor environment. Semaphorins, a large family of secreted and membrane-bound proteins, have emerged to be an important regulator of several biological processes (such as vascular, cancer and neurodevelopment), cell morphology and leukocyte trafficking [56,57]. Of interest to us, Semaphorin 3E (its cognate receptor, plexin D1) has been reported to regulate negatively the secretion of IL-12 in DC, a primary cytokine to regulate NK cell activation [58].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%